2015
DOI: 10.3109/23744235.2015.1040445
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacterial osteomyelitis

Abstract: Osteomyelitis caused by nontuberculous mycobacteria (NTM) can have severe consequences and a poor prognosis. Physicians therefore need to be alert to this condition, especially in immunocompromised patients. Although the pathogenesis of NTM osteomyelitis is still unclear, studies in immunodeficient individuals have revealed close relationships between NTM osteomyelitis and defects associated with the interleukin-12–interferon-γ–tumor necrosis factor-α axis, as well as human immunodeficiency virus infection, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 186 publications
1
38
1
2
Order By: Relevance
“…In our experience, this is not the case except in mycobacterial osteomyelitis where samples may need specific culture mediums 42 and can be treated with antibiotic therapy alone. 43 , 44 Romano's classification may be intended for descriptive purposes only, and to the best of our knowledge, has not been validated clinically. Others reported that the number and type of organism are reported not to have a bearing on the outcome of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, this is not the case except in mycobacterial osteomyelitis where samples may need specific culture mediums 42 and can be treated with antibiotic therapy alone. 43 , 44 Romano's classification may be intended for descriptive purposes only, and to the best of our knowledge, has not been validated clinically. Others reported that the number and type of organism are reported not to have a bearing on the outcome of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically important species by group include Mycobacterium kansasii and Mycobacterium marinum (Group I); Mycobacterium gordonae and Mycobacterium scrofulaceum (Group II); Mycobacterium avium intracellulare and Mycobacterium ulcerans (Group III); and M. fortuitum , M. chelonae , Mycobacterium abscessus (Group IV) 311. Out of these, NTM strains often acquired by trauma are M. fortuitum , M. chelonae , and M. marinum 221…”
Section: Discussionmentioning
confidence: 99%
“…In a study from 1998 to 2011, 29 patients were diagnosed with musculoskeletal NTM infection (4). The treatment for NTM osteomyelitis is complicated requiring surgical debridement and long term chemotherapy (14). It is important to identify the NTM up to species level as the management is considerably different for different species.…”
Section: Discussionmentioning
confidence: 99%